Identifying social and economic barriers to regular care and treatment for Black men who have sex with men and women (BMSMW) and who are living with HIV: a qualitative study from the Bruthas cohort. Issue 1 (December 2017) - Arnold, Emily; Weeks, John; Benjamin, Michael; Stewart, William; Pollack, Lance; Kegeles, Susan; Operario, Don
Abstract Background There is little research regarding the ability of Black men who have sex with men and women (BMSMW) to access and maintain HIV-related health care and treatment adherence. This population, who often insist on secrecy about their same-sex desire, may experience unique barriers to seeking regular care and treatment. Methods From March 2011-April 2014, we recruited 396 BMSMW in the San Francisco Bay Area to be enrolled in our randomized controlled trial. At baseline we administered a behavioral survey assessing: demographics, homelessness, employment, history of incarceration, HIV status and disclosure practices, care and treatment adherence. 64 men reported living with HIV at intake. To learn more about their experiences, we recruitedN  = 25 to participate in qualitative interviews, which were conducted April-December 2014. Topics included: current living situation, diagnosis story, disclosure practices, experiences of accessing and maintaining care and treatment, and HIV-related stigma. Recordings were transcribed and coded for major themes. Results Despite being located in an area where treatment is plentiful, men faced social and economic barriers to maintaining regular care and treatment adherence. Several findings emerged to shed light on this quandary: (1) Competing needs particularly around attaining stable housing, food security, and money created barriers to treatment and care; (2) Side effects of HIV medications discouraged men from adhering to treatment; (3) Provider and Institutional level characteristics influenced care engagement; (4) Disclosure and social support made a difference in care and treatment behaviors; and (5) Participants expressed a desire for group-based intervention activities to support treatment and care among HIV+ BMSMW. Inadequate engagement in the continuum of care for HIV was born out in the quantitative data where 28% of participants did not know their Viral Load. Conclusions A holistic approach to HIV health for BMSMW would appear to translate to better outcomes for men living with HIV, where a goal of viral suppression must also include attending to their basic social and economic support needs.